A bioaugmentation agent allowing the advanced treatment of refractory refinery wastewater in a biological aerated filter and analysis of its microbial community. Issue 4 (22nd January 2020) - Feng, Lei; He, Qingsheng; Wen, Jianping
Abstract: BACKGROUND: The performance of a biological aerated filter (BAF) with activated sludge and nut shell activated carbon was evaluated for the advanced treatment of intractable refinery wastewater. Bioaugmenting the BAF with Pseudomonas sp. FS‐01 and Bacillus sp. FS‐02 and the microbial community structure between the upgrade system and the original system were also studied. RESULTS: During the steady state of the BAF, the influent chemical oxygen demand (COD) was in the range 80–128 mg L −1, and ammonia nitrogen (NH4 + ‐N) was in the range 15–20 mg L −1 . The BAF with activated carbon from nut shells as a supporting material can remove over 32% of influent COD and 95% of NH4 + ‐N. On bioaugmentation, the average effluent COD and NH4 + ‐N concentrations were 31.8 and 0.4 mg L −1, respectively. The predominant genera in BAF1 were Nitrospira, an unranked member of the Anaerolineaceae and an unclassified member of the Rhizobiales, while the dominant genera in BAF2 were Pseudomonas, Bacillus and an unranked member of the Anaerolineaceae. CONCLUSIONS: The coconut shell activated carbon has outstanding properties for removing COD and NH4 + ‐N, along with high shock loading resistance. Bioaugmentation can improve the COD remove efficiency by 35% in relation to only adding sludge. Microbial diversity analysis indicated that bioaugmentation accelerated the transformation of the bacterial community structure, quickly becoming dominant strains. This bioaugmented process may be a promising alternative technology for the treatment of refractory wastewater. © 2019 Society of Chemical Industry